Accuracy and safety of robotic navigation-assisted distraction osteogenesis for hemifacial microsomia - Zhang, Ziwei; Zhao, Zhijie; Han, Wenqing; Kim, Byeong Seop; Yan, Yingjie; Chen, Xiaojun; Lin, Li; Shen, Weimin; Chai, Gang (Frontiers in Pediatrics, 2023)
This study aimed to verify the accuracy and safety of distraction osteogenesis for hemifacial microsomia assisted by a robotic navigation system based on artificial intelligence. The small sample early-phase single-arm clinical study, available at http://www.chictr.org.cn/index.aspx, included children aged three years and older diagnosed with unilateral hemifacial microsomia (Pruzansky-Kaban type II). A preoperative design was performed, and an intelligent robotic navigation system assisted in the intraoperative osteotomy. The primary outcome was the accuracy of distraction osteogenesis, including the positional and angular errors of the osteotomy plane and the distractor, by comparing the preoperative design plan with the actual images one week postoperatively. Perioperative indicators, pain scales, satisfaction scales, and complications at one week were also analyzed. Four cases (mean 6.5 years, 3 type IIa and 1 type IIb deformity) were included. According to the craniofacial images one week after surgery, the osteotomy plane positional error was 1.77 ± 0.12 mm, and the angular error was 8.94 ± 4.13°. The positional error of the distractor was 3.67±0.23 mm, and the angular error was 8.13±2.73°. Postoperative patient satisfaction was high, and no adverse events occurred. The robotic navigation-assisted distraction osteogenesis in hemifacial microsomia is safe, and the operational precision meets clinical requirements. Its clinical application potential is to be further explored and validated.